Promoção de saúde a idosos institucionalizados da cidade de Araçatuba SP - Marquesi, Camila [UNESP]; Rovida, Tânia Adas Saliba [UNESP]; Moimaz, Suzely Adas Saliba [UNESP]; Garbin, Cléa Adas Saliba [UNESP]; Saliba, Nemre Adas [UNESP] (Universidade Estadual Paulista (Unesp), 2015)
The aging of the population is a reality that has taken place due to the great advancement of technology and the consequent improvement in quality of life. Thus there is need for training of professionals to provide adequately meet the health needs of the population. Based on this, the FOA- UNESP, develops an extension project (health promotion will institutionalized elderly in the city of Araçatuba- SP), since 1999, this work order was to present the project and its main results. Which aims socialization of institutionalized elderly through group dynamics, promotion and prevention of oral and general health, clinical care and promote the humanization of dental care. The program meets the four nursing homes of Araçatuba- SP:. Ismael Shelter, Home of Old Age and Asylum St. Vincent de Paul and Asylum St. John are held trainings and lectures with caregivers to maintain oral health, through meetings, lectures and practical training, clinical weekly to raise the dental needs and rehabilitation. It is concluded that the most satisfactory result is to improve the quality of life of the elderly, and raising the self-esteem of them, qualifications of caregivers and learning of the project participants.

O envelhecimento da população brasileira é uma realidade que vem ocorrendo devido ao grande avanço da tecnologia e conseqüente melhoria na qualidade de vida. Dessa forma há necessidade de capacitação dos profissionais para proporcionar de maneira adequada o atendimento das necessidades de saúde da população. Com base nisto, a FOA- UNESP, desenvolve um projeto de extensão (promoção de saúde á idosos institucionalizados da cidade de Araçatuba- SP), desde o ano de 1999, neste trabalho o objetivo foi apresentar o projeto e seus principais resultados. Que tem como objetivos a socialização dos idosos institucionalizados por meio de dinâmica de grupo, promoção e prevenção de saúde bucal e geral, atendimento clínico e promover a humanização no atendimento odontológico. O programa atende as quatro instituições asilares de Araçatuba- SP: Abrigo Ismael, Lar da Velhice e Asilo São Vicente de Paulo e Asilo São João. São realizadas capacitações e palestras com os cuidadores para a manutenção da saúde bucal, por meio de reuniões, palestras e treinamentos práticos, exames clínicos semanalmente para levantar as necessidades de tratamento odontológico e reabilitadores. Concluise que o resultado mais satisfatório é a melhoria na qualidade de vida destes idosos, e a elevação da auto-estima dos mesmos, qualificação dos cuidadores e aprendizagem dos participantes do projeto.
Keywords: Aging; Quality of life; Health promotion; Envelhecimento; Qualidade de vida; Promoção da saúde